Caudal lumbar disc disease presenting as 'praying position'‐like posture and gait. Issue 1 (3rd February 2015) - Espadas, Irene; Chai, Orit; Lindley, Samantha; Wessmann, Annette
Abstract : A 10‐year‐old Border collie and a five‐year‐old Domestic shorthaired cat are reported with a 'praying'‐like posture as clinical presentation for caudal lumbar disc disease. Neurological examination localised to L6‐S3 spinal cord segments or nerve roots. Advanced diagnostic imaging revealed disc herniations at L7‐S1 vertebrae in the dog and at L6‐L7 vertebrae in the cat. The dog improved significantly with conservative treatment whereas the cat underwent a decompressive dorsal laminectomy followed by complete resolution of his clinical signs. This unusual posture leads to increased space for the cauda equina within the vertebral canal by widening the caudal lumbar intervertebral spaces and thus suspected to alleviate the pain more successfully compared with a normal posture. A 'praying position'‐like posture has not been reported as a clinical manifestation for caudal lumbar disc disease in a dog and a cat, yet should be considered as a differential diagnosis for this unusual pain relief posture.